Beyond product placement - Bianca Wright (Communicare)
In South Africa, advergaming currently does not reach a mass audience because of the low number of Internet users and the high cost of Internet access. However, as a brand communication tool, advergaming has the potential to be used as a viral marketing tactic. The article analyses the potential of the mobile environment as a catalyst for enabling the use of advergaming as a viral marketing tool in South Africa and proposes a theoretical model derived from an analysis of existing literature and observation, for operationalising mobile advergaming.